Distinctive Properties of Strongly Magic Square - C. K. Neeradha; V. Madhukar Mallayya (International Journal of Mathematics And its Applications, 2016)
Magic squares have turned up throughout history, some in a mathematical context and others in philosophical or religious contexts.A magic square is a square array of numbers where the rows, columns, diagonals and co-diagonals add up to the same number. The paper discuss about a well-known class of magic squares; the strongly magic square. The strongly magic square is a magic square with a stronger property that the sum of the entries of the sub-squares taken without any gaps between the rows or columns is also the magic constant. In this paper a generic definition for Strongly Magic Squares is given.Some advanced mathematical properties of strongly magic squares is also discussed.